Evaluate the predictors of post-caesarean section pain level and Analgesic consumption: Impact of Anesthesia and Patient Demography. - Sodee kirshan, Nusrat Lakho, Fareeda Islam, Shahneela Perveen , Sayyada Humaira Masood , Pavan Kumar , Sonia khan, Ghulam Abbas Shah, Maryam, Madiha memon, Misha Fatima, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Pain is a significant health concern worldwide, with chronic pain being a majorcontributor to disability. It is considered the fifth vital sign, and its impact on quality of life is substantial. Pregnancy is a physiological